Disaster Nursing Learning Outcomes: What Do Evidences Inform - Etika Emaliyawati; Kusman Ibrahim; Yanny Trisyani (Universitas Padjadjaran, 2022)
The increase of disaster events almost in many countries has been raising concern among nurse educators to review, evaluate, and integrate the disaster knowledge and skills into nursing curricula. Currently, most nursing schools developed the disaster nursing curriculum based on the guideline given by the International Council of Nurses (ICN). However, adaptation and development of local context of the population need to be taken into account in order to fit with the local needs and situation. This study aims to systematically review the existing literature concerning the disaster nursing learning outcomes applied in nursing education. Published articles in database of EBSCOhost, PubMed and Google Scholar were retrieved using the keywords: “learning outcome”, “disaster nursing”, “disaster management”. Of 201 articles were obtained then screened for the inclusion criteria such as written in English or Bahasa, available in fulltext version, and being published no last than 10 years back. Nine articles met the criteria and then systematically reviewed. The study found that disaster nursing learning outcomes include; the understanding of disaster management by applying knowledge, technology, planning, risk analysis, and management techniques to deal with disasters; developing competencies for each phase of disaster; acquiring skills and knowledge by evaluating, assessing and combining data, utilizing current evidence-based strategies; analyzing and evaluating public administration. This study concluded that it is important to determine evidence-based disaster nursing learning outcomes that fit with the local context and conditions, especially in Indonesia.